Sequential double quantum blind signature protocol - Hui WANG; Run-hua SHI; Hong ZHONG; Jie CUI; Shun ZHANG; Kai-ting WANG (Tongxin xuebao)
Considering the fact that both party banks need to sign on the same bill because of the inter-bank E-payment in real life.A sequential double blind signature protocol based on the quantum coherence and quantum entanglement was proposed for the first time.Consumer blinded the message at first and each bank signed the blinded message one by one.The advantage of this protocol is that it only requires particle measurements for the verification without any quantum unitary operation.In addition,the proposed protocol obtains the higher efficiency and accuracy in the phase of signature verification,compared with other single quantum blind signature schemes.